Pelatihan Peningkatan Kualitas Media Pembelajaran Pendidik Menggunakan Platform Canva di SILN Bangkok - Setiawan, Aditya Chandra; Haq, Mohammad Syahidul; Choirunnisa , Nadia Lutfi; Widayanti, Melia Dwi; Anggraeny, Diah (Universitas Negeri Surabaya, 2024)
The community partner for the year 2024 is located in SILN Bangkok, Thailand. The challenges faced by the partner include suboptimal utilization of technology and digitalization in the development of educational media. This condition serves as the basis for community service implementation, where the research team possesses specific expertise in educational institution management, particularly the issues faced by institutions in SILN Bangkok. Based on the priority issues faced by the partner, the agreed-upon method is training. In addition to direct training, the method used includes online mentoring to help the partner develop engaging and innovative educational media. The mandatory outcomes are Mass Media News and Activity Videos. The results obtained indicate that SILN Bangkok partners have gained an improvement in understanding and skills related to the quality of educational media using the Canva platform through 32 hours of training and mentoring, both online and offline, and have received a satisfaction indicator in the